Modelo para computação da irrigação suplementar e do número de dias trabalháveis com máquinas agrícolas na produção da soja (Glycine max (L.) Merril) - C Sediyama, Gilberto; O Pruitt, William; N da Costa, José Maria; Bernardo, Salassier (Revista Ceres, 2025)
The model containing stochastic components has proved to be a powerful tool in simulation of soil moisture balance, supplemental irrigation water requirements and days suitable for machinery operations.